Pendidikan Islam di Era Revolusi Industri 4.0 - Suharto (STAI Terpadu Yogyakarta, 2019)
This paper is motivated by the condition of Islamic Education as an important subject in forming the noble values of students. Islam as a system of belief and belief greatly influences actualization in the context of education. The formulation of the problem posed is